2016
DOI: 10.4238/gmr.15038604
|View full text |Cite
|
Sign up to set email alerts
|

Association of ectomycorrhizal fungi with Picea crassifolia (Pinaceae, Piceoidae) from high-altitude stands in Mount Helan Nature Reserve, China

Abstract: ABSTRACT. We investigated the diversity of ectomycorrhiza associated with the endemic Picea crassifolia in Mount Helan National Nature Reserve in Inner Mongolia, China. Toward this objective, we conducted morphological and molecular identification of ectomycorrhizae in soil cubes taken from pure P. crassifolia stands. Eleven types of ectomycorrhizal (ECM) organisms were separated, briefly described, and identified. Nine morphotypes belonged to the The diversity of ECM organisms in P. crassifolia was lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…High-throughput sequencing technology has greatly facilitated the acquisition of genome data (Li et al, 2020), which allows us to investigate the ecophysiology of uncultured microbes (Wagner, 2009). In our study, the number of ECM species (196 OTUs) detected that were associated with P. crassifolia from the region of Inner Mongolia (NM group) is much higher than 11 OTUs at the same site (Fan et al, 2016). A total of 10 ECM species (all except 1) were found using both methods (Table 4).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…High-throughput sequencing technology has greatly facilitated the acquisition of genome data (Li et al, 2020), which allows us to investigate the ecophysiology of uncultured microbes (Wagner, 2009). In our study, the number of ECM species (196 OTUs) detected that were associated with P. crassifolia from the region of Inner Mongolia (NM group) is much higher than 11 OTUs at the same site (Fan et al, 2016). A total of 10 ECM species (all except 1) were found using both methods (Table 4).…”
Section: Discussionmentioning
confidence: 72%
“…Our results clearly showed Tomentella was the most species-rich genus ahead of Cortinarius , Inocybe , and Sebacina . However, none of Tomentella species was detected using Sanger sequencing ( Fan et al, 2016 ). Thus, relative to Sanger sequencing, high-throughput sequencing can capture a greater proportion of species, which is considered to be more effective in the field of community ecology ( Paul et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The high abundance of Piloderma indicated that it might contribute to the initial establishment of T. sutchuenensis in mountainous areas, and the differentiation pattern of topsoil fungal communities with altitude might be a strategy for habitat adaptation of T. sutchuenensis . Some members of Cortinarius play a key role in mobilizing nutrients from organic matter and accelerating N cycling at high altitudes ( 58 , 59 ). With elevation, the soil physicochemical properties (i.e., OM, WC, N, and K) increased, so that the fungal community changed from stress-resistant taxa (i.e., Tomentella ) to vegetative taxa (i.e., Piloderma and Cortinarius ).…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al examined the ECM fungi associated with Picea crassifolia in Mt. Helan [25], however the soil type was uncertain. Hence, the distribution of ECM fungal species in Asian subarctic limestone areas remains poorly known.…”
Section: Introductionmentioning
confidence: 99%